2004
DOI: 10.1037/0022-006x.72.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Versus Integrative Behavioral Couple Therapy for Significantly and Chronically Distressed Married Couples.

Abstract: A randomized clinical trial compared the effects of traditional behavioral couple therapy (TBCT) and integrative behavioral couple therapy (IBCT) on 134 seriously and chronically distressed married couples, stratified into moderately and severely distressed groups. Couples in IBCT made steady improvements in satisfaction throughout the course of treatment, whereas TBCT couples improved more quickly than IBCT couples early in treatment but then, in contrast to the IBCT group, plateaued later in treatment. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
396
7
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(424 citation statements)
references
References 53 publications
(76 reference statements)
8
396
7
4
Order By: Relevance
“…IBCT was designed to decrease negative interactions among partners by emphasizing emotional acceptance (Christensen et al, 2004). In contrast to traditional behavioral couple therapy (TBCT), which seeks to change behavior of spouses, the goal of IBCT is to help spouses accept, without promoting resignation, aspects of their partners that were previously unacceptable (Jacobson, Christensen, Prince, Cordova, & Eldridge, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IBCT was designed to decrease negative interactions among partners by emphasizing emotional acceptance (Christensen et al, 2004). In contrast to traditional behavioral couple therapy (TBCT), which seeks to change behavior of spouses, the goal of IBCT is to help spouses accept, without promoting resignation, aspects of their partners that were previously unacceptable (Jacobson, Christensen, Prince, Cordova, & Eldridge, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this technique is to help family members learn to talk about their problems without engaging in conflicts. It also encourages family members to recognize that certain aspects of their relative are unchangeable, such as bipolar illness, and to be accepting rather than pushing them to change.IBCT has been shown to significantly improve relationship satisfaction and to decrease global distress among couples (Christensen et al, 2004). Of more relevance, IBCT interventions have been shown to produce large increases in nonblaming discussions as compared to TBCT (Cordova et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobson, Christensen, Prince, Cordova, and Eldrige (2000) found that approximately 80% of couples responded to normal functioning in the IBCT group. On follow up, 67% of couples significantly improved their relationships for two years (Christensen, Atkins, Berns, Wheeler, Baucom, & Simpson, 2004). While 67% of couples in therapy experiencing clinically significant reliable change are a powerful effect, IBCT continues to refine its tenets and its treatment formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining the validity of the DAS has shown that total DAS scores have been consistently shown to discriminate between distressed and nondistressed couples and have been shown to identify couples with a high likelihood of divorce (Crane, Busby, & Larson, 1991). A cut-score of 97.5 has been validated to identify relationship distress (Christensen et al, 2004). The validity of the subscales has been assessed by examining the correlations between the DAS subscales and measures of love, liking, and marital satisfaction across heterosexual married and gay and lesbian cohabiting couples (Kurdek, 1992).…”
Section: Relationship Satisfactionmentioning
confidence: 99%